Using Conditional Sentences in Domestic Violence Cases: A New Brunswick Exploration - Gill, Carmen; Thériault, Luc (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
Conditional sentencing was introduced in Canada in 1996 and has since gained momentum in the justice system as an alternative to incarceration. The New Brunswick Advisory Council on the Status of Women (2006) reports a growing use of conditional sentences in woman abuse cases as well as a decrease in the average jail time imposed on convicted abusers. In this article, we explore the use of conditional sentencing in the Province of New Brunswick, comparing domestic violence cases for which a conditional sentence was issued against a random sample of domestic violence cases from the year 2004. Key variables examined included the nature of the previous criminal record (if any) of the accused, the level of violence used, the perception the victim has of her safety, and the relationship between the victim and the accused. Results indicate that none of the selected variables had a significant effect on the use of conditional sentencing. La peine avec sursis a Ctk introduite au Canada en 1996; depuis, elle s’est progressivement imposCe dans le systkme judiciaire comme une alternative 5 l’incarc6ration. Le Conseil consultatif sur la condition de la femme du Nouveau- Brunswick (2006) signale un usage croissant des peines avec sursis dans les cas de violence contre les femmes ainsi qu’une diminution de la duree moyenne de l’incarckration imposee aux agresseurs condamnks. Dans cet article, nous explorons l’usage de la peine avec sursis dans la province du Nouveau-Brunswick ell comparantles cas de violence domestique recevant une peine avec sursis a un Cchantillon de cas de violence domestiques pris au hasard 2 partir de 2004. Les variables essentielles examinees comprennent la nature du casier judiciaire antCc6dent de 1’accusC (s’il y a lieu), la gravitC de la violence utilisee, la perception de la victime quant a sa sCcurit6 et la relation entre la victime et l’accuse. Les rksultats indiquent qu’aucune de ces variables sClectionnCes n’a eu un effet important sur l’usage de la peine avec sursis.